Exploring the detoxification effects and mechanism of Caowu in prescription using liquid chromatography-high-resolution mass spectrometry-based metabolomics - Li Wang; Hui Dong; Ai-hua Zhang; Ying Han; Tai-ping Li; Le Yang; Hui Sun; Xiang-cai Meng; Xi-jun Wang (Open Journal of Proteomics and Genomics - Peertechz Publications, 2018)
Liquid chromatography/mass spectrometry-based metabolomics analyses have been used in the evaluation of drug toxicity and finding detoxification methods. Yunnan Baiyao (YNBY) is a famous prescription for its effects on traumatic blood stasis in China. However, the adverse reactions of YNBY including anaphylactic shock, arrhythmia and renal failure hindered its further development due to Aconite kusnezoffii Radix. (caowu) in YNBY. The purpose of our research is to study the safety of YNBY compatibility of caowu for 4 weeks on SD rats by oral administration. In this study, we determined the toxic effects on rats by conducting examinations of histopathological and clinical physiological and biochemical indicators. Next, we prospectively analyzed known metabolites using an untargeted approach in serum SD rats administrated with YNBY and NCY (caowu replaced by excipient from YNBY) respectively for four weeks by mass spectrometry analysis. As a result, we found caowu in YNBY had no toxicity on rats according to general toxicological evaluations. It was no obvious difference between administration and control groups on AKP, GOT, GPT, BUN, CK, MDA and LDH, except Na+/K+-ATPase (ATP) and SOD index. NCY had a greater influence on rats than YNBY according to metabolism. In this study, we found 77 biomarkers in YNBY and 110 biomarker of NCY, involved 12 and 20 metabolic pathways respectively. L-arginine, palmitic acid, oleic acid and stearic acid both in YNBY and NCY could participated in liver necrosis/cell death including apoptosis of hepatocytes, cell death of hepatocytes and lipoapoptosis of hepatocytes, which predicted by Ingenuity pathway Analysis (IPA). Of note, betaine produced by YNBY and cholic acid produced by NCY merely contributed to cell death of hepatocytes by prediction. Our findings based on metabolite profiles were that, caowu is safe existed in YNBY during four weeks. Caowu promoted the function of energy metabolism in heart and protecting the heart from oxygen free radicals. Betaine produced by YNBY and cholic acid produced by NCY may play a role in cell death of hepatocytes.